Photosynthetic and Photoprotective Responses to Steady-State and Fluctuating Light in the Shade-Demanding Crop Amorphophallus xiei Grown in Intercropping and Monoculture Systems - Zhang, Jinyan; Shuang, Shengpu; Zhang, Ling; Xie, Shiqing; Chen, Junwen (Frontiers in Plant Science, 2021)
Photosynthetic and photoprotective responses to simulated sunflecks were examined in the shade-demanding crop Amorphophallus xiei intercropped with maize (intercropping condition) or grown in an adjacent open site (monoculture condition). Both intercropped leaves and monoculture leaves exhibited very fast induction responses. The times taken to achieve 90% maximum net photosynthetic rate in intercropped leaves and monoculture leaves were 198.3±27.4 s and 223.7±20.5 s during the photosynthetic induction, respectively. During an 8-min simulated sunfleck, the proportion of excess excited energy dissipated through the xanthophyll cycle-dependent pathway (NPQ) and dissipated through constitutive thermal dissipation and the fluorescence (f, d) pathway increased quickly to its maximum, and then plateaued slowly to a steady state in both intercropped and monocultured leaves. When the illumination was gradually increased within photosystem II (PSII), NPQ increased quicker and to a higher level in monocultured leaves than in intercropped leaves. Relative to their monocultured counterparts, intercropped leaves exhibited a significantly lower accumulation of oxygen free radicals, a significantly higher content of chlorophyll, and a similar content of malondialdehyde. Although monocultured leaves exhibited a larger mass-based pool size of xanthophyll cycle [V (violaxanthin) +A (antheraxanthin) + Z (zeaxanthin)] than intercropped leaves, intercropped leaves had a higher ratio of (Z+A)/(V+Z+A) than monocultured leaves. Intercropped leaves had markedly higher glutathione content and ascorbate-peroxidase activity than their monocultured counterparts. Similar activities of catalase, peroxidase, dehydroascorbate reductase, and monodehydroascorbate were found in both systems. Only superoxide dismutase activity and ascorbate content were lower in the intercropped leaves than in their monocultured counterparts. Overall, the xanthophyll cycle-dependent energy dissipation and the enzymatic antioxidant defense system are important for protecting plants from photooxidation in an intercropping system with intense sunflecks.